Living on the Edge: Youth Entry, Career and Exit in Drug-Selling Gangs - Leandro Carvalho; Rodrigo R. Soares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
We use data from a unique survey of members of drug-trafficking gangs in favelas (slums) of Rio de Janeiro, Brazil, to characterize drug-trafficking jobs and study the selection into gangs, analyzing what distinguishes gang-members from other youth living in favelas. We also estimate wage regressions for gang-members and examine their career path: age at entry, progression within the gangs' hierarchy, and short- to medium-term outcomes. Individuals from lower socioeconomic background and with no religious affiliation have higher probability of joining a gang, while those with problems at school and early use of drugs join the gang at younger ages. Wages within the gang do not depend on education, but are increasing with experience and involvement in gang-related violence. The two-year mortality rate in the sample of gang-members reaches 20%, with the probability of death increasing with initial involvement in gang violence and with personality traits associated with unruliness.
Keywords: J4; K42; O15; O17; 330; Jugendkriminalität; Drogenwirtschaft; Soziale Gruppe